Fremdkörper - Pratschke, Katja (Germany : Kunsthoschule fur medien Koln, 2002)
In "Transposed Bodies", a prize-winning photofilm, two inseparable friends and their love for the same girl captivate the spectator. Jan, a student of Philosophy falls in love with Marie and the two are expecting a baby. As the relationship grows sour, Marie is increasingly aware of Jan's friend Jon, who seems to possess all the qualities missing in Jan. After a tragic car accident, the two friends undergo an operation, which results in a bizarre mishap - now Jon's head is sewn to Jan's body and vice versa. Who is the father of the baby about to be born? Whom does Marie love now? Katja Pratschke tells a dramatic love story without moving images; it is a rediscovery of the graphic novel genre on screen.
Keywords: Fiction films